Entrepreneurship Education Research Opportunities based on the Global University Entrepreneurship Students’ Spirit Survey (GUESSS): A Conceptual Research Design - Suhartanto, Eko (Research Synergy Foundation, 2024)
Entrepreneurship education evidently can influence entrepreneurial intention and career choices among university students, but its effectiveness varies across contexts. Thus, further exploration to understand the interplay between entrepreneurship education and relevant interference factors is urgently needed. The objective of this paper is to highlight research avenues that leverage GUESSS data to examine factors impacting the relationship between entrepreneurship education and career transitions, family business succession, and entrepreneurial activities. The study adopts a conceptual research design that utilizes GUESSS data collected from university students worldwide. The data offer insights into students’ entrepreneurial activities, career choices, and family business involvement. Findings suggest significant research potential in examining the moderating effects of individual and environmental factors on entrepreneurship education's impact. The paper concludes by proposing research models to explore these dynamics, thus contributing to the broader entrepreneurship education literature. The novelty of this study lies in its introduction of GUESSS as a comprehensive cross-country data source, enabling new research opportunities. Its potential contribution to the body of knowledge includes advancing theoretical models on the interaction between entrepreneurship education, individual traits, and environmental factors. This study also opens doors for further empirical validation and collaboration among academic researchers worldwide.